A rapid hemostatic sponge with water-triggered shape memory property and bleeding monitoring function and a preparation method thereof
Patent Information
- Application Number
- CN202610874312.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-23
AI Technical Summary
但纤维素的电导率较低,限制其在智能止血中的应用
[0009]本发明通过季铵化纤维素的正电季铵基团与羧基化纤维素纳米纤维的负电羧酸基团之间的静电相互作用,以及柠檬酸与纤维素分子链上羟基之间的酯键交联,构建了稳定的三维网络结构,有效提高了海绵的力学性能和结构稳定性;该海绵中大量的羟基、羧基等亲水性基团赋予海绵优异的亲水性,结合冷冻干燥形成的毛细管通道,该海绵具备高效吸液能力,有助于浓缩血液中的凝血物质,通过负电羧酸基团激活内源性凝血途径,加速血凝块形成;季铵化纤维素赋予海绵液体触发形状记忆特性,结合高效吸液能力,压缩后的海绵在接触血液后能够迅速吸收血液并恢复初始形状,可以有效填充不可压缩的深部伤口,作为物理屏障堵塞血管;该海绵中正电季铵基团通过静电吸附破坏细菌细胞膜结构导致内容物外泄,柠檬酸通过降低细菌内部pH值,破坏DNA和蛋白质,二者协同赋予海绵对革大肠杆菌和金黄色葡萄球菌的抑菌能力,有效降低伤口感染风险;碳纳米管在羧基化纤维素纳米纤维和超声的协同作用下均匀分散在体系中,作为导电填料赋予海绵良好的导电性。海绵吸收血液后,内部导电网络随着吸收量改变而发生电阻变化,实现对伤口出血状态的实时监测。
Smart Images

Figure CN122955014A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical engineering hemostatic materials technology, specifically relating to a rapid hemostatic sponge with water-triggered shape memory properties and bleeding monitoring function, and its preparation method. Background Technology
[0002] While hemostasis is a natural and immediate physiological response, it can be extremely difficult to buy patients valuable time for emergency treatment in cases of uncontrolled massive bleeding. In many surgical procedures, such as liver, spine, cardiovascular, and orthopedic surgeries, uncontrolled massive bleeding is unavoidable. Therefore, hemostatic materials are crucial for effective hemostasis and improving patient survival rates. Traditional hemostatic materials, such as gauze, gelatin sponges, and bone wax, often achieve hemostasis through pressure and absorption, but this can have several adverse effects, such as a high rebleeding rate, hindered wound healing, and difficulty in removal.
[0003] Shape memory sponges are common smart deformation-responsive materials that typically expand within wounds by absorbing liquid and restoring their original shape through liquid-triggered shape recovery, rapidly applying pressure to the wound surface for quick hemostasis. Compared to the absorption and clogging effects of traditional hemostatic materials, novel water-triggered shape memory sponges not only offer advantages such as high-speed liquid absorption and rapid expansion, but also, through material design, promote blood cell adhesion and facilitate coagulation cascades. The sponge's porous structure promotes blood absorption, blood cell aggregation, and the capture of coagulation factors, making it effective for hemostasis in incompressible wounds. Introducing conductivity into water-triggered shape memory hemostatic sponges is an innovative design in the field of biomaterials, with significance extending beyond hemostasis to enhance dynamic monitoring and synergistic treatment functions through electrical properties.
[0004] The quaternary ammonium groups in quaternized cellulose carry a positive charge, which can interact with the negatively charged surface of bacteria, thereby effectively inhibiting bacterial growth. The hydrophilicity and hygroscopicity of quaternized cellulose enhance its hemostatic effect. Carboxylated cellulose nanofibers, due to their small size and large specific surface area, can enhance the overall mechanical strength of the material. Their carboxyl (-COOH) groups can form hydrogen bonds with water molecules, thereby improving the absorbency of the sponge. Furthermore, the carboxyl groups can also provide a locally negatively charged surface, activating the intrinsic coagulation pathway and capturing positively charged fibrinogen and calcium ions through electrostatic interactions. 2+This further promotes blood clot formation. Cellulose-based hemostatic sponges not only possess high porosity, high hydrophilicity, and biocompatibility, but also promote the concentration of blood cells and coagulation substances, achieving rapid hemostasis. However, the low electrical conductivity of cellulose limits its application in intelligent hemostasis. Carbon nanotubes (CNTs) exhibit excellent electrical conductivity and near-infrared stimulus response, and can also promote the concentration of coagulation substances in hemostatic materials and induce platelet activation. Therefore, developing CNT-enhanced intelligent shape memory cellulose-based hemostatic sponges for deep, incompressible wound hemostasis is a promising approach. Summary of the Invention
[0005] In order to overcome the limitations of existing hemostatic materials, this invention provides a rapid hemostatic sponge with water-triggered shape memory properties and bleeding monitoring function.
[0006] This invention is achieved by the following technical solution: a water-triggered shape memory and bleeding monitoring rapid hemostatic sponge, wherein the hemostatic sponge uses quaternized cellulose (QC) as the matrix, carboxylated cellulose nanofibers (CNF) assisting in the ultrasonic dispersion of carbon nanotubes (CNTs) as the reinforcing material, and is prepared by esterifying and crosslinking cellulose with citric acid (CA), combined with freeze-drying and thermal crosslinking processes; wherein, the positively charged quaternary ammonium groups of quaternized cellulose form electrostatic interactions with the negatively charged carboxylic acid groups of carboxylated cellulose nanofibers, the carbon nanotubes and carboxylated cellulose nanofibers are stably dispersed through non-covalent π-π stacking, citric acid crosslinks the cellulose molecular chains through ester bonds, and combined with the abundant hydrogen bonds in the system, a porous hemostatic sponge is constructed.
[0007] A method for preparing the rapid hemostatic sponge with water-triggered shape memory properties and bleeding monitoring function includes the following steps: (1) Preparation of carboxylated cellulose nanofiber / carbon nanotube slurry: 0.1 g of carbon nanotubes were added to 20 mL of 1% w / v carboxylated cellulose nanofiber suspension, and the mixture was magnetically stirred for 30 min and then ultrasonically treated for 30 min to obtain carboxylated cellulose nanofiber / carbon nanotube slurry. (2) Preparation of quaternized cellulose solution: Disperse quaternized cellulose in deionized water and stir until homogeneous to form a quaternized cellulose solution with a concentration of 3% w / v; (3) Mixing: Add 0.05g of carboxylated cellulose nanofibers to the quaternized cellulose solution obtained in step (2), stir thoroughly, then add 5mL of the carboxylated cellulose nanofiber / carbon nanotube slurry obtained in step (1) and stir evenly. (4) Preparation of sponge precursor solution: Under the heating condition of 80℃ water bath, add 0.05g citric acid to the mixed solution obtained in step (3), heat and react for 1h, and stir evenly to obtain sponge precursor solution; (5) Preparation of rapid hemostatic sponge: The sponge precursor solution obtained in step (4) is freeze-dried. The method is as follows: the sponge precursor solution is poured into a 24-well plate and pre-frozen at -20℃ for 24h to obtain a pre-frozen sponge precursor. Then, it is freeze-dried in a vacuum freeze dryer at -50~-60℃ and a vacuum degree of 10~20Pa for 48h. Subsequently, it is heat-crosslinked at 120℃ for 2h to obtain the rapid hemostatic sponge.
[0008] In step (2), 0.6g of quaternized cellulose is dispersed in 20ml of deionized water.
[0009] This invention constructs a stable three-dimensional network structure through the electrostatic interaction between the positively charged quaternary ammonium groups of quaternized cellulose and the negatively charged carboxylic acid groups of carboxylated cellulose nanofibers, as well as the ester bond crosslinking between citric acid and the hydroxyl groups on the cellulose molecular chain. This effectively improves the mechanical properties and structural stability of the sponge. The abundant hydrophilic groups such as hydroxyl and carboxyl groups in the sponge endow it with excellent hydrophilicity. Combined with the capillary channels formed by freeze-drying, the sponge possesses highly efficient liquid absorption capacity, which helps to concentrate clotting substances in blood. The negatively charged carboxylic acid groups activate the intrinsic coagulation pathway, accelerating blood clot formation. Quaternized cellulose imparts liquid-triggered shape memory to the sponge. Combining its unique shape-memory properties with highly efficient liquid absorption, the compressed sponge rapidly absorbs blood upon contact and returns to its initial shape, effectively filling incompressible deep wounds and acting as a physical barrier to block blood vessels. The positively charged quaternary ammonium groups in the sponge disrupt bacterial cell membrane structures through electrostatic adsorption, causing leakage of contents. Citric acid lowers the internal pH of bacteria, damaging DNA and proteins. These two factors synergistically endow the sponge with antibacterial properties against *Escherichia coli* and *Staphylococcus aureus*, effectively reducing the risk of wound infection. Carbon nanotubes, uniformly dispersed in the system through the synergistic effect of carboxylated cellulose nanofibers and ultrasound, act as a conductive filler, giving the sponge excellent conductivity. After absorbing blood, the internal conductive network changes its resistance with the amount absorbed, enabling real-time monitoring of the wound's bleeding status.
[0010] This invention constructs a rapid hemostatic sponge with water-triggered shape memory properties and bleeding monitoring function. The sponge utilizes electrostatic interactions, ester crosslinking, and hydrogen bond networks, combined with freeze-drying and thermal crosslinking processes to synergistically construct a stable porous structure. This hemostatic sponge can be used not only for surface hemostasis but also for deep bleeding in incompressible soft tissues. The complex capillary porous channels promote rapid blood absorption and coagulation substance aggregation, forming a physical barrier to block damaged blood vessels, providing a good foundation for rapid hemostasis. Positively charged quaternary ammonium groups attract blood cells through electrostatic interactions, while negatively charged carboxylic acid groups activate the intrinsic coagulation pathway, thereby promoting the coagulation cascade and inducing rapid clot formation. The sponge possesses antibacterial properties, effectively inhibiting the proliferation of *Escherichia coli* and *Staphylococcus aureus*. The sponge prepared by this invention can also provide real-time feedback on bleeding status through changes in electrical resistance, providing objective evidence for clinical hemostasis assessment. Therefore, the rapid hemostatic sponge with water-triggered shape memory properties and bleeding monitoring function of this invention has excellent application prospects in hemostasis of incompressible wounds, bleeding monitoring, and wound protection. Attached Figure Description
[0011] Figure 1 This is the infrared spectrum of the hemostatic sponge used in this invention; Figure 2 In the image: A is a scanning electron microscope (SEM) image of the QCFTA hemostatic sponge in Example 1; B is a scanning electron microscope (SEM) image of the QC hemostatic sponge in Comparative Example 1; C is a scanning electron microscope (SEM) image of the QCA hemostatic sponge in Comparative Example 2; D is a scanning electron microscope (SEM) image of the QCFA hemostatic sponge in Comparative Example 3. Figure 3 The porosity experiment of the hemostatic sponge in this invention; Figure 4 This invention relates to a blood absorption experiment using a hemostatic sponge. Figure 5 This invention relates to a water-triggered shape memory experiment of a hemostatic sponge. Figure 6 This invention relates to an experiment on the shape recovery rate of the hemostatic sponge. Figure 7 Ten 80% cycle compression experiments were conducted on the hemostatic sponge used in this invention. Figure 8 This invention relates to an antibacterial experiment on the hemostatic sponge. Figure 9 This invention provides a biocompatibility experiment of the hemostatic sponge. Figure 10 This invention relates to an in vitro coagulation experiment of the hemostatic sponge. Figure 11 This invention provides an evaluation experiment of the coagulation cascade of the hemostatic sponge. Figure 12 This invention relates to a bleeding monitoring experiment using a hemostatic sponge. Figure 13 This invention provides an experimental model of femoral artery puncture and bleeding using the hemostatic sponge in this invention. Figure 14 This invention relates to an experimental model of liver defect bleeding in rats using the hemostatic sponge. Detailed Implementation
[0012] To more clearly present the purpose, technical concept, and advantages of the specific embodiments of the present invention, some exemplary solutions will be described in detail below. It should be understood that the examples described are only some representative examples of the possible embodiments of the present invention, and not all embodiments. Based on the technical concept described in the present invention, other implementations that can be obtained by those skilled in the art without inventive effort all fall within the scope of the claims of this technology.
[0013] All technical terms and nouns used in this document have the same meaning as commonly understood by one of ordinary skill in the art, unless otherwise specified herein. All publicly cited materials and materials cited by them are incorporated herein by reference.
[0014] For those skilled in the art, equivalent technical solutions to the embodiments described herein, which can be derived from the content of this specification and in conjunction with conventional experimental methods, are all covered within the scope of this application.
[0015] Unless otherwise specified, the experimental procedures involved in the specific embodiments described below are all conventional experimental methods in the relevant technical field; the instruments and equipment used are all standard laboratory configurations; and all kinds of chemical reagents and biological raw materials used can be purchased through conventional commercial channels unless otherwise specified.
[0016] Example 1: A method for preparing a rapid hemostatic sponge with water-triggered shape memory properties and bleeding monitoring function, comprising the following steps: Carboxylated cellulose nanofibers were prepared into a 20 mL 1% w / v suspension. 0.1 g of carbon nanotube powder was added, and the mixture was stirred thoroughly before ultrasonic treatment to obtain a carboxylated cellulose nanofiber / carbon nanotube slurry. Quaternized cellulose was dispersed in deionized water and stirred thoroughly to form a 3% (w / v) quaternized cellulose solution. 0.05 g of carboxylated cellulose nanofibers were introduced into a 20 mL quaternized cellulose solution, followed by 5 mL of the carboxylated cellulose nanofiber / carbon nanotube slurry, and stirred thoroughly. 0.05 g of citric acid was added under heating at 80 °C. After thorough stirring, the resulting solution was poured into a 24-well plate, pre-frozen at -20 °C, and then freeze-dried under vacuum for 48 h. The freeze-dried sponge was then placed in a 120 °C oven for 2 h to obtain a rapid hemostatic sponge, abbreviated as QCFTA.
[0017] The obtained hemostatic sponge was subjected to infrared spectroscopy detection, and the results are as follows: Figure 1 As shown, 2914cm -1 The peak at 1477 cm⁻¹ represents the stretching vibration of CH, a characteristic peak of the cellulose skeleton. -1 The peak at this point is the asymmetric bending vibration peak of N-CH3, which corresponds to the quaternization group ((CH3)3N). + The characteristic peaks of -) indicate that all materials retain the basic structure of quaternized cellulose. 1722cm -1 The characteristic peaks are C=O stretching vibrations, which can characterize the ester bonds (-COOR) formed by the esterification crosslinking between the hydroxyl groups of cellulose and the carboxyl groups of citric acid, as well as the carboxyl groups (-COOH) of carboxylated cellulose nanofibers.
[0018] The obtained hemostatic sponge was scanned by electron microscopy, and the results are as follows: Figure 2 As shown, Figure 2 As shown in Figure A, under the combined effects of electrostatic interactions, ester bonds, and hydrogen bonds, the degree of cross-linking of the sponge gradually increases, the cross-linking network becomes denser, and a porous sponge with an interconnected network structure is formed.
[0019] Comparative Example 1: This Comparative Example 1 provides a quaternized cellulose hemostatic sponge (QC). The specific method is as follows: Quaternized cellulose is dispersed in deionized water and stirred until a 3% (w / v) quaternized cellulose solution is formed. The resulting solution is poured into a 24-well plate, pre-frozen at -20℃, and then freeze-dried under vacuum for 48 hours to obtain the quaternized cellulose hemostatic sponge (QC). Electron microscopy was performed on the QC, and the results are as follows... Figure 2 As shown in Figure B, the porous structure of the QC sponge is relatively loose in the SEM image.
[0020] Comparative Example 2: This comparative example provides a preparation of a quaternized cellulose / citric acid hemostatic sponge, comprising the following steps: quaternized cellulose is dispersed in deionized water and stirred thoroughly to form a 3% (w / v) quaternized cellulose solution. 0.05 g of citric acid is added under heating at 80°C. After stirring evenly, the resulting solution is poured into a 24-well plate, pre-frozen at -20°C, and then freeze-dried under vacuum for 48 h. The freeze-dried sponge is then placed in a 120°C oven for 2 h to obtain the quaternized cellulose / citric acid hemostatic sponge (QCA).
[0021] The obtained QCA was scanned by electron microscopy, and the results are as follows: Figure 2 As shown in C, the esterification and cross-linking process of citric acid and cellulose significantly affects the cross-linking density of the sponge. The QCA sponge forms a denser three-dimensional network structure with a significantly reduced pore size.
[0022] Comparative Example 3: This comparative example provides a method for preparing a quaternized cellulose / carboxylated cellulose nanofiber / citric acid hemostatic sponge. The main difference from Example 1 is that no carboxylated cellulose nanofiber / carbon nanotube slurry was added. The method includes the following steps: Quaternized cellulose is dispersed in deionized water and stirred thoroughly to form a 3% (w / v) quaternized cellulose solution. 0.05 g of carboxylated cellulose nanofibers are introduced into 20 mL of the quaternized cellulose solution and stirred thoroughly. 0.05 g of citric acid is added under heating at 80°C. After stirring evenly, the resulting solution is poured into a 24-well plate, pre-frozen at -20°C, and freeze-dried under vacuum for 48 h. The freeze-dried sponge is then placed in a 120°C oven for 2 h to obtain the quaternized cellulose / carboxylated cellulose nanofiber / citric acid hemostatic sponge (QCFA).
[0023] The obtained QCFA was scanned by electron microscopy, and the results are as follows: Figure 2 As shown in Figure D, the QC sponge exhibits a loose, macroporous structure. Citric acid undergoes esterification and cross-linking with cellulose, introducing CNFs and CNTs to form electrostatic interactions and hydrogen bonds within the composite. These interactions collectively increase the cross-linking density of the sponge, resulting in a more compact structure.
[0024] Porosity experiment of hemostatic sponges: Porosity experiments were conducted on the hemostatic sponges QC, QCA, QCFA, and QCFTA obtained from Comparative Examples 1, 2, and 3 and Example 1. The porosity of different sponges was determined using the ethanol substitution method. The initial mass and volume of the dried sponge were recorded, and it was completely immersed in ethanol. After the ethanol was absorbed to saturation, the sponge was removed, and excess ethanol was wiped off with filter paper.
[0025] Specific test results are as follows: Figure 3 The porosities of the QC sponges in Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 1 (QCFA) and QCFTA sponges in Example 1 were 77.76 ± 4.13 mg / cm³, respectively. 3 87.45±3.03mg / cm 3 84.93±2.53mg / cm 3 78.45±3.22mg / cm 3 The esterification and cross-linking between citric acid and cellulose in QCA forms a denser three-dimensional network structure, resulting in a significant reduction in pore size and an increase in porosity. However, upon further introduction of CNFs and CNTs, multiple interactions within the system, such as the electrostatic interactions between quaternary ammonium groups and carboxyl groups, the π-π stacking between CNTs and CNFs, and the hydrogen bonds formed by numerous hydroxyl and carboxyl groups, lead to a thicker and denser pore wall. This further compresses the three-dimensional network structure of the sponge, resulting in thicker pore walls, a smaller pore size, and consequently, a decrease in porosity. Consequently, the overall porosity of the QCFTA sponge decreases to 78.45 ± 3.22 mg / cm³.3 However, QCFTA still maintains a high porosity, indicating that it still has abundant interconnected channels and a high liquid absorption capacity, which can meet the needs of rapid blood absorption and hemostasis. At the same time, the denser structure is also conducive to improving the mechanical stability of the sponge.
[0026] Blood absorption performance test of hemostatic sponges: The hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, 3, and Example 1 were subjected to a blood absorption performance test. The dried sponges were compressed and immersed in deionized water or blood. The sponges were removed from the blood and weighed at different test times.
[0027] Specific test results are as follows: Figure 4 The QC sponges in Comparative Example 1, QCA in Comparative Example 2, QCFA in Comparative Example 3, and QCFTA sponges in Example 1 all exhibited good blood absorption capacity. However, the absorption capacity of the sponges decreased significantly after cross-linking with citric acid, and the densification of the internal network structure of the QCA sponge hindered water penetration. The introduction of CNF brought more hydrophilic carboxyl groups (-COOH), thus improving the hydrophilicity of the sponge. Finally, the QCFTA sponge obtained in Example 1 showed good liquid absorption performance, with blood absorption capacities of 45.07±1.24 g / g, 34.05±2.05 g / g, 42.28±2.30 g / g, and 40.94±0.57 g / g respectively after 60 seconds.
[0028] Water, PBS, and Blood Triggered Shape Recovery Performance Tests of Hemostatic Sponges: The hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, and 3, and Example 1, were subjected to water, PBS, and blood triggered shape recovery tests. Each group of sponges was forcefully compressed to fully fix their shape. The fixed-shape sponges were then immersed in water, PBS, and fresh whole blood to restore their shape. The initial state, compressed state, and water and blood triggered shape recovery states of the sponges were recorded.
[0029] Specific test results are as follows: Figure 5 During the evaluation of the water and blood-triggered shape memory properties of the QC of Comparative Example 1, QCA of Comparative Example 2, QCFA of Comparative Example 3, and QCFTA of Example 1, it was observed that the dry sponge could maintain its compressed shape after being squeezed. Subsequently, the sponge was allowed to absorb deionized water, PBS, and blood, respectively. The liquid rapidly penetrated into the internal pores of the sponge, and the collapsed pore structure re-expanded, restoring it to a near-original shape. The sponge exhibited good deionized water, PBS, and blood-triggered shape memory properties. The sponge could still quickly rebound after being folded and compressed and injected into water, indicating that deionized water, PBS, and blood-triggered shape memory has good repeatability and adaptability, and has the potential for hemostasis of deep, incompressible wounds.
[0030] Water-triggered shape recovery rate experiment of hemostatic sponges: The hemostatic sponges QC, QCA, QCFA, and QCFTA obtained from Comparative Examples 1, 2, 3, and Example 1 were subjected to a water-triggered shape recovery rate experiment. The initial length of the sponge was measured, and the sponge was fully compressed and held in this state for 5 minutes to ensure that the sponge was fully compressed. Then the sponge was immersed in deionized water to fully absorb water until it completely recovered its shape, and the height was measured.
[0031] Specific test results are as follows: Figure 6 Comparative Examples 1, 2, 3, and Example 1 showed that the sponges were subjected to external pressure for a period of time to fully absorb water until they returned to a stable shape. The water-triggered shape recovery rates of the hemostatic sponges QC, QCA, QCFA, and QCFTA in Example 1 were 88.55±6.92%, 107.35±10.04%, 115.92±7.21%, and 111.97±6.39%, respectively. The large number of hydrophilic groups in the QCFTA sponge enabled it to quickly absorb liquid and form new hydrogen bonds upon re-contact with water after compression. The electrostatic interaction between QC and CNF, the π-π interaction between CNF and CNTs, the esterification crosslinking between CA and cellulose chains, and the numerous hydrogen bonds within the system collectively constructed a stable three-dimensional network framework, allowing the sponge to quickly recover its original pore structure after the external force was released. Because the pore walls and pore volume of the sponge further expanded after water absorption, the water-triggered shape recovery rate exceeded 100%. This indicates that QCFTA sponges possess excellent water-triggered shape recovery properties, restoring their original shape and maintaining their integrity after absorbing a large amount of water. This makes them useful for deep, incompressible wounds, enabling immediate pressure hemostasis.
[0032] Cyclic compression test of hemostatic sponges: The hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, and 3 and Example 1 were subjected to cyclic compression tests. The mechanical properties of the sponges were evaluated using a universal testing machine. In the cyclic compression test, the wet sponge was compressed to 80% strain at a rate of 10 mm / min, and the cycle was repeated 10 times.
[0033] Specific test results are as follows: Figure 7 The QCFTA sponge in Example 1 maintained its intact shape during 10 cycles of water absorption and loss, exhibiting the best initial strength, high resilience, and rapid recovery behavior. Covalent cross-linking significantly enhances the mechanical stability of the QCFTA sponge, and the reinforcing effect of nanomaterials further assists in improving the mechanical properties of the QCFTA sponge network, preventing the highly elastic sponge from failing during repeated deformation.
[0034] Antibacterial test of hemostatic sponges: Antibacterial tests were conducted on the hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Examples 1, 2, and 3 and Example 1. The antibacterial properties of the hemostatic hydrogels were tested using *Escherichia coli* (ATCC 25922) and *Staphylococcus aureus* (ATCC 43300). 20 mg of each of the QC, QCA, QCFA, and QCFTA sponges were sterilized under UV light. Solid and liquid culture media were prepared separately and sterilized in an autoclave. *Escherichia coli* and *Staphylococcus aureus* were inoculated into the liquid culture medium and agitated thoroughly. The mixture was incubated at 37°C for 24 h to obtain the bacterial stock solution, which was then serially diluted. 1 mL of the diluted bacterial suspension was aspirated into a 24-well plate, and then the samples were added sequentially to the wells. The plates were incubated at 37°C for 24 h. After 24 hours, 100 μL of the co-cultured bacterial suspension was transferred to a 96-well plate, and the OD value was measured at 595 nm using an iMark microplate reader (Bio-Rad Laboratories, Inc.). Another 100 μL of the bacterial suspension was added to solid culture medium and spread evenly. The plates were incubated at 37°C for 24 hours, and then photographed and counted.
[0035] Specific test results are as follows: Figure 8 The bacterial activity of the hemostatic sponges QC, QCA, QCFA, and QCFTA groups obtained from Examples 1, 2, and 3 (using the plate coating method) after one day of co-culturing with *Escherichia coli* (54.28±11.11%, 18.86±4.85%, 6.73±2.83%, 0.65±1.13%) and *Staphylococcus aureus* (32.03±8.20%, 1.81±0.96%, 0.90±0.84%, 0.63±0.56%) was determined. The OD values of the *E. coli* and *Staphylococcus aureus* suspensions at 595 nm were further measured. The results showed that the antibacterial activity of the QC and QCA sponges was increased compared to the control group, while the antibacterial effect of the QCFA and QCFTA sponge groups did not change significantly. This is mainly because the positively charged quaternary ammonium groups can attract the negative charge on the bacterial cell membrane surface, thereby disrupting the cell membrane structure and causing intracellular substances to leak out. Citric acid has been shown to lower the internal pH of bacteria, damage their DNA and proteins, and ultimately cause them to die.
[0036] Biocompatibility assay of hemostatic sponges: Biocompatibility assays were performed on the QC, QCA, QCFA, and QCFTA hemostatic sponges used in Comparative Examples 1, 2, 3, and Example 1. Mouse fibroblast L929 cell viability was assessed using the Cell Counting Kit-8 (CCK-8). L929 cells were seeded in 96-well plates at a concentration of 10,000 cells / well. Sponge extract culture medium was prepared using sterilized sponges and incubated with L929 cells for 1, 3, and 5 days. The control group was incubated with complete culture medium only. CCK-8 solution was added to the wells at predetermined time points, and the cells were incubated at 37°C for 2 hours. Absorbance was measured at 450 nm using an iMark enzyme labeler (Bio-Rad Laboratories, Inc.). L929 cell viability was assessed using a Calcein-AM / PI double staining kit. L929 cells were seeded in 24-well plates at a concentration of 5000 cells / well and co-cultured with different sample extracts for 1, 3, and 5 days. Live / dead cell staining was performed at predetermined time points, and the cells were incubated at 37°C for 30 min. Cell morphology was observed using a fluorescence microscope.
[0037] Specific test results are as follows: Figure 9 After L929 cells were co-cultured with extracts of hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, and 3, and Example 1 for 1, 3, and 5 days, under a fluorescence microscope, the vast majority of cells exhibited green fluorescence (live cells), while red fluorescence (dead cells) was less common. The morphology of L929 cells in each group was observed to be normal and intact. The CCK-8 assay results showed that the proliferation rate of L929 cells in each group of quaternized cellulose-based sponges was higher than 80%, and no significant toxicity was observed. All these results indicate that the QCFTA sponge described in Example 1 has good cell compatibility.
[0038] Blood Coagulation Index (BCI) Test for Hemostatic Sponges: The hemostatic properties of the hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, 3, and Example 1 were evaluated using the coagulation index. 20 mg of sponge samples were placed in 10 mL centrifuge tubes and preheated at 37°C for 10 min. 180 μL of fresh anticoagulated blood and 20 μL of activated blood prepared with 0.1 mol / L CaCl2 were added to the centrifuge tubes, and the mixture was incubated at 37°C for 10 min. For the experimental group, 5 mL of deionized water was used to wash the material along the wall. For the negative control group, 200 μL of activated blood was mixed with 5 mL of deionized water. Finally, the supernatants from both the experimental and negative control groups were collected, and the absorbance was measured at 595 nm.
[0039] Test results as follows Figure 10The blood coagulation index (BCI) can further quantify the hemostatic ability of hemostatic materials. The BCI values of the hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, and 3 and Example 1 were 75.49±1.42%, 25.15±3.19%, 19.60±5.53%, 19.15±3.49%, and 14.60±3.01%, respectively. The BCI value of QCFTA sponge was significantly lower than that of the other sponges. QCFTA sponge has high porosity and interconnected porous channels, which can quickly absorb water from the blood and promote the local concentration of clotting substances at the wound surface. The abundant carboxyl and hydroxyl groups and the rough porous structure in the sponge can further enhance the adhesion and aggregation of blood components. At the same time, the introduction of CNTs helps to improve the stability of the network structure, allowing the sponge to maintain its pores and support function after absorbing blood. Therefore, QCFTA can form stable blood clots more quickly, shorten clotting time and reduce BCI value, indicating that QCFTA hemostatic sponge has an effective coagulation-promoting effect.
[0040] Activated Partial Thromboplastin Time (APTT) Assay for Hemostatic Sponges: The coagulation mechanism of the hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in Comparative Examples 1, 2, 3, and Example 1 was evaluated using the activated partial thromboplastin time (APTT) assay. Anticoagulated whole blood was centrifuged at 3000 rpm for 10 min, and the supernatant anemic platelet-rich plasma (PPP) was collected. The sponge sample was added to 50 μL of PPP and 50 μL of APTT reagent and co-incubated at 37 °C for 3 min. Subsequently, 50 μL of 0.025 mol / L CaCl2 was added, and the activated partial thromboplastin time (s) was measured using a semi-automatic coagulation analyzer (MTN-II, Marton Medical, Changchun, China).
[0041] Specific test results are as follows: Figure 11 The APTT values of the hemostatic sponges QC, QCA, QCFA, and QCFTA obtained in the blank group, Comparative Examples 1, 2, and 3, and Example 1 were 44.87±0.477s, 42.23±1.07s, 36.30±3.80s, 23.97±3.97s, and 18.83±3.59s, respectively. The significant difference between QCFTA and the blank group indicates that QCFTA has a significant effect on the intrinsic coagulation pathway. The intrinsic coagulation pathway can usually be activated by contact with negatively charged or foreign surfaces. The negatively charged carboxylic acid groups of QCFTA sponge help initiate the intrinsic coagulation cascade reaction. The porous structure of the sponge can also rapidly absorb plasma water, concentrate coagulation factors and blood cells. Therefore, QCFTA can enhance the intrinsic coagulation pathway and further strengthen the hemostatic effect.
[0042] Bleeding monitoring experiment of hemostatic sponges: The bleeding monitoring capabilities of the hemostatic sponges obtained in Comparative Examples 1, 2, 3, and Example 1 (QC, QCA, QCFA, QCFTA) were evaluated using an SB100A-20 / 21 four-probe analyzer. The sponges were cut into square pieces, and the conductivity changes of the hemostatic sponge from Example 1 after absorbing 50, 100, 150, 200, and 250 μL of blood were tested using the four-probe analyzer. The sponge samples were placed on the test stage of the four-probe analyzer with a probe spacing of 1.59 mm. The probe spacing was adjusted so that the probes were tangent to the sample surface, and the conductivity of the sponge was then measured.
[0043] Specific test results are as follows: Figure 12 As the amount of blood absorbed increased, the conductivity of the QCFTA sponge in Example 1 continuously increased with a significant trend, reaching 1.10 ± 0.13 S / m after absorbing 250 μL of blood. Measuring the conductivity changes of the QCFTA sponge at different blood absorption levels can be used to predict wound hemostasis.
[0044] Experimental study of a rat femoral artery puncture hemorrhage model using hemostatic sponge: The hemostatic sponge QCFTA obtained in Example 1 was used to create a rat femoral artery puncture hemorrhage model. Rats were anesthetized and fixed on a surgical board. The sponge and filter paper were weighed and recorded. In the rat femoral artery puncture hemorrhage model, a puncture wound was created using a rat femoral artery needle, causing bleeding. The hemostatic sponge was applied to the bleeding site. The amount of blood loss and the time to hemostasis were recorded.
[0045] Specific test results are as follows: Figure 13 A femoral artery puncture bleeding model was established in rats. The bleeding point was formed by needle puncture and accompanied by rapid blood seepage. The amount of bleeding in the femoral puncture bleeding model of the QCFTA sponge in Example 1 was 80.63±26.46mg, and the hemostasis time was 112.86±8.79s.
[0046] Rat liver perforation hemorrhage model experiment using hemostatic sponge: The hemostatic sponge QCFTA obtained in Example 1 was used to create a rat liver perforation hemorrhage model experiment. Rats were fixed on an operating table and the liver was exposed through an abdominal incision. Pre-weighed filter paper was placed under the liver and an 8 mm circular penetrating wound was formed using a biopsy punch to induce bleeding. The wound was filled with fully compressed QCFTA sponge, and the total blood loss and hemostasis time were recorded.
[0047] Specific test results are as follows: Figure 14The hemostatic ability of QCFTA sponge in Example 1 was evaluated using a rat liver perforation and hemorrhage model. An 8mm penetrating cylindrical defect was created in the rat liver to establish the model. After local liver resection, a large amount of blood oozed from the wound. The QCFTA sponge, after being fully compressed, was injected into the defect cavity via a syringe. It absorbed the blood and expanded, fully filling the defect. This process significantly improved the hemostatic effect on the rat liver perforation wound, with blood loss and hemostasis time of 688.63±137.75 mg and 94.60±9.74 s, respectively.
[0048] The above experimental results confirm that the QCFTA sponge prepared in this invention possesses excellent water-triggered shape memory properties. When the sponge is squeezed or folded in a dry state, the internal pores temporarily collapse, and the cellulose molecular chains fix their temporary shape through hydrogen bonds. When used for bleeding from incompressible wounds, the compressed sponge can quickly absorb blood, which rapidly enters the pores of the sponge, causing the collapsed pores to reopen. Therefore, the sponge can quickly recover its shape under liquid stimulation, thus adapting to hemostasis of deep, incompressible wounds and enhancing the effects of blood absorption, packing, and compression hemostasis. The complex capillary channels promote rapid blood absorption and the aggregation of clotting substances. The positively charged quaternary ammonium groups can attract blood cells through electrostatic interactions, while the negatively charged carboxylic acid groups can activate the intrinsic coagulation pathway, accelerating blood clot formation. Simultaneously, the sponge possesses antibacterial properties, preventing microbial infection of the wound. The QCFTA sponge has good electrical conductivity, allowing for real-time feedback of the bleeding status through changes in resistance. Therefore, the rapid hemostatic sponge of this invention has potential applications in both rapid hemostasis and bleeding monitoring.
[0049] Finally, it should be noted that the specific embodiments listed above are merely illustrative of the technical concept of the present invention and do not constitute a significant limitation on the present invention. Although the present invention has been described in detail based on the above embodiments, those skilled in the art should understand that modifications can be made to the content described in the foregoing embodiments, or some or all of the technical features can be replaced with functionally equivalent alternatives, without departing from the core content of the present invention. Such modifications or substitutions, as long as they do not cause the substantive content of the corresponding technical solution to depart from the protection scope of the claims of the present invention, are all considered to fall within the scope of the present invention.
Claims
1. A rapid hemostatic sponge with water-triggered shape memory and bleeding monitoring functions, characterized in that: The hemostatic sponge uses quaternized cellulose (QC) as the matrix and carboxylated cellulose nanofibers (CNF) as the reinforcing material to assist in the ultrasonic dispersion of carbon nanotubes (CNTs). It is prepared by cross-linking cellulose with citric acid (CA) and combining freeze-drying and thermal cross-linking processes. In this process, the positively charged quaternary ammonium groups of quaternized cellulose form an electrostatic interaction with the negatively charged carboxylic acid groups of carboxylated cellulose nanofibers. The carbon nanotubes and carboxylated cellulose nanofibers are stably dispersed through non-covalent π-π stacking. Citric acid cross-links the cellulose molecular chains through ester bonds, and the rapid hemostatic sponge is constructed by combining the hydrogen bond interactions within the system.
2. A method for preparing the water-triggered shape memory and bleeding monitoring rapid hemostatic sponge of claim 1, characterized in that: Includes the following steps: (1) Preparation of carboxylated cellulose nanofiber / carbon nanotube slurry: 0.1 g of carbon nanotubes were added to 20 mL of 1% w / v carboxylated cellulose nanofiber suspension, and the mixture was magnetically stirred for 30 min and then ultrasonically treated for 30 min to obtain carboxylated cellulose nanofiber / carbon nanotube slurry. (2) Preparation of quaternized cellulose solution: Disperse quaternized cellulose in deionized water and stir until homogeneous to form a quaternized cellulose solution with a concentration of 3% w / v; (3) Mixing: Add 0.05g of carboxylated cellulose nanofibers to the quaternized cellulose solution obtained in step (2), stir thoroughly, then add 5mL of the carboxylated cellulose nanofiber / carbon nanotube slurry obtained in step (1) and stir evenly. (4) Preparation of sponge precursor solution: Under the heating condition of 80℃ water bath, add 0.05g citric acid to the mixed solution obtained in step (3), heat and react for 1h, and stir evenly to obtain sponge precursor solution; (5) Preparation of rapid hemostatic sponge: The sponge precursor solution obtained in step (4) is freeze-dried. The method is as follows: the sponge precursor solution is poured into a 24-well plate and pre-frozen at -20℃ for 24h to obtain a pre-frozen sponge precursor. Then, it is freeze-dried in a vacuum freeze dryer at -50~-60℃ and a vacuum degree of 10~20Pa for 48h. Subsequently, it is heat-crosslinked at 120℃ for 2h to obtain the rapid hemostatic sponge.
3. The preparation method according to claim 2, characterized in that: In step (2), 0.6g of quaternized cellulose is dispersed in 20ml of deionized water.